2004
DOI: 10.1021/la048559q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Organic Matter at Mineral/Water Interfaces:  3. Implications of Surface Dissolution for Adsorption of Oxalate

Abstract: The adsorption of oxalate on a model aluminum oxide, corundum (alpha-Al2O3), has been examined over a broad range of oxalate concentrations (0.125-25.0 mM) and pH conditions (2-10). In situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) measurements indicate that at low to intermediate concentrations ([oxalate] < or = 2.50 mM), oxalate adsorbs to corundum predominantly as a bidentate, mononuclear, inner-sphere complex involving both carboxyl groups. Significant contributions from outer-sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 75 publications
16
85
0
Order By: Relevance
“…Dozens of recent studies reveal complexity in structure and speciation of adsorbed organics, particularly through in situ FTIR and other spectroscopic studies (Somasundaran and Krishnakumar 1994;Rodriguez et al 1996;Holmen et al 1997;Roddick-Lanzilotta et al 1998;Fitts et al 1999;Klug and Forsling 1999;Kubicki et al 1999;McQuillan 1999, 2000;Duckworth and Martin 2001;Sheals et al 2002;Lackovic et al 2003;Rosenqvist et al 2003;Yoon et al 2004Yoon et al , 2005Johnson et al 2004aJohnson et al , 2004bJohnson et al , 2004cJohnson et al , 2005aJohnson et al , 2005b (Thomas et al 1993;Orme et al 2001;Asthagiri and Hazen 2007). In addition, for the calcite-water interface, many theoretical simulations and observations exist to guide surface chemical models (Stipp and Hochella 1991;Parker 1997, 1999;Teng et al 1998Teng et al , 2000Fenter et al 2000;Wright et al 2001;Stipp 2002;de Leeuw and Cooper 2004;Geissbuhler et al 2004;Kristensen et al 2004).…”
Section: Mineral Surfacesmentioning
confidence: 99%
“…Dozens of recent studies reveal complexity in structure and speciation of adsorbed organics, particularly through in situ FTIR and other spectroscopic studies (Somasundaran and Krishnakumar 1994;Rodriguez et al 1996;Holmen et al 1997;Roddick-Lanzilotta et al 1998;Fitts et al 1999;Klug and Forsling 1999;Kubicki et al 1999;McQuillan 1999, 2000;Duckworth and Martin 2001;Sheals et al 2002;Lackovic et al 2003;Rosenqvist et al 2003;Yoon et al 2004Yoon et al , 2005Johnson et al 2004aJohnson et al , 2004bJohnson et al , 2004cJohnson et al , 2005aJohnson et al , 2005b (Thomas et al 1993;Orme et al 2001;Asthagiri and Hazen 2007). In addition, for the calcite-water interface, many theoretical simulations and observations exist to guide surface chemical models (Stipp and Hochella 1991;Parker 1997, 1999;Teng et al 1998Teng et al , 2000Fenter et al 2000;Wright et al 2001;Stipp 2002;de Leeuw and Cooper 2004;Geissbuhler et al 2004;Kristensen et al 2004).…”
Section: Mineral Surfacesmentioning
confidence: 99%
“…These play an important role in aquatic and soil chemistry (Biber and Stumm 1994). Numerous studies have been reported on the adsorption of these organic acids on clay minerals and metal oxides Dzombak 1998 andFilius et al 1997;Horanyi 2002;Johnson et al 2004;Kang and Xing 2007;Kirwan, et al 2003;Xu and Ji 2003). The present study can also help to reveal the role of the LMM OAs in the environmental chemistry of Hg.…”
mentioning
confidence: 75%
“…A competition thus occurs between particles and NOM for binding Hg(II) (Arias et al 2004;Singh et al 1996). NOM can also bind to particles (Johnson et al 2004;Schuster 1991) and affect Hg(II) distribution between particles and solutions. Particle-ligand-Hg(II) thus forms an interesting ternary system in aquatic systems and soils.…”
mentioning
confidence: 99%
“…ATR-FTIR is arguably the spectroscopic technique of choice for deriving molecular-scale information on the attachment geometry of organic molecules at solid-water interfaces (Hind et al ., 2001) as demonstrated by Per Persson (Umeå University) and co-workers (e.g., Axe et al ., 2006;Boily et al ., 2000) . In a series of in situ ATR-FTIR studies, we examined the interaction of (1) oxalate (C 2 O 4 2-) with a-Al 2 O 3 (corundum) and g-AlOOH (boehmite) Johnson et al ., 2004b), (2) (Johnson et al ., 2005a)…”
Section: Adsorption Of Organic Molecules At Mineral-water Interfaces mentioning
confidence: 99%